DIGITAL VISUAL IN HUMANITIES (CULTURОLOGICAL ASPECT) - Пархоменко, Андрій (SWorldJournal, 2025)
The aim of the article is to investigate the cultural aspect of the involvement of the digitized visual (digitization of visual information and digital data visualizations) in modern humanities by determining the role of the digital visual in the methodol